2012
DOI: 10.1016/j.plaphy.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Increased de novo riboflavin synthesis and hydrolysis of FMN are involved in riboflavin secretion from Hyoscyamus albus hairy roots under iron deficiency

Abstract: Riboflavin secretion by Hyoscyamus albus hairy roots under Fe deficiency was examined to determine where riboflavin is produced and whether production occurs via an enhancement of riboflavin biosynthesis or a stimulation of flavin mononucleotide (FMN) hydrolysis. Confocal fluorescent microscopy showed that riboflavin was mainly localized in the epidermis and cortex of the root tip and, at the cellular level, in the apoplast. The expressions of three genes involved in the de novo biosynthesis of riboflavin (GTP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…It has been reported that iron deficiency induces riboflavin biosynthesis and secretion in the roots of some plants. This would make riboflavin available as a nutrient or signal molecule for bacteria in the rhizosphere (39)(40)(41). It is tempting to speculate that bacteria harboring a riboflavin transporter, in addition to a complete riboflavin biosynthesis pathway, are able to economize in synthesizing riboflavin when it is available from the environment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that iron deficiency induces riboflavin biosynthesis and secretion in the roots of some plants. This would make riboflavin available as a nutrient or signal molecule for bacteria in the rhizosphere (39)(40)(41). It is tempting to speculate that bacteria harboring a riboflavin transporter, in addition to a complete riboflavin biosynthesis pathway, are able to economize in synthesizing riboflavin when it is available from the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, temperature extremes, high light levels, pH excursions, and stress-driven accumulations Table I. of metabolites with which cofactors react all directly accelerate diverse types of spontaneous cofactor damage (Treadwell and Metzler, 1972;Baggott, 2000;Mills et al, 2006;Marbaix et al, 2011). Abiotic stresses can also promote cofactor damage indirectly by altering compartmentation (Akhtar et al, 2010;Mohammadi et al, 2012) by inducing enzymes that break down cofactors (Rapala-Kozik et al, 2008;Higa et al, 2012) and by creating harsh cellular conditions in which enzymes that normally act on other substrates become more promiscuous (Piedrafita et al, 2015) and mistakenly attack cofactors. Figure 1 uses color-coded arrows to show the site and nature of damage reactions that vitamins and cofactors can undergo in physiological conditions, and Table I catalogs the reactions corresponding to the arrows.…”
Section: Chemical and Metabolic Lability: Why Bad Things Happen To Gomentioning
confidence: 99%
“…In the case of Cyp80F1, primer pairs were used, according to the previous report (Li et al, 2006). The expression of riboflavin synthase ( RibD ) was also determined as a representative gene involved in riboflavin biosynthesis, according to our previous report (GenBank accession, AB712370) (Higa et al, 2012). Primers used were as follows: H6H , forward (5′-GGTCTCTTTCAGGTGATCAA-3′) and reverse (5′-CTTCACAGATGTAGTCCAGCA-3′); Cyp80F1 , forward (5′-CACAGTTGAATGGACATTGGTGGAGC-3′) and reverse (5′-GAACAGTAATGGCGCCGGAGGATGC-3′); RibD , forward (5′-GTTGTCGGAATTTAGTGTCGG-3′) and reverse (5′-TCCCAGTCTTGACCTTCACC-3′).…”
Section: Methodsmentioning
confidence: 99%
“…It is noteworthy that complexes I and II contain a large number of Fe ions, whilst AOX does not contribute to the generation of a proton gradient (Ohnishi, 1998; Taiz and Zeiger, 2002; Vigani et al, 2009). On this basis, we have proposed that riboflavin secretion occurs as a result of the underuse of flavoprotein complexes I and/or II (Higa et al, 2010), although both increased de novo riboflavin synthesis and hydrolysis of FMN could be involved in riboflavin secretion (Higa et al, 2012). On the other hand, it has been proposed that flavins accumulated in the roots may act as electron donors or as cofactors for Fe (III) reductase (López-Millán et al, 2000; Rodríguez-Celma et al, 2011a,b), because the Fe reductase contains FAD as a cofactor (Schagerlöf et al, 2006).…”
Section: Introductionmentioning
confidence: 99%